Analisis Dan Mitigasi Resiko Rantai Pasok Dengan Metode AHP Dan FMEA - Wiwik Handayani; Muhammad Adam Yusuf (Universitas Islam Kadiri, 2022)
During the Covid-19 pandemic, the economy in Indonesia experienced a decline, especially MSMEs. It is important for MSMEs to switch strategies in dealing with this pandemic, one of which is by using an online system in the sales process, as was done by MSMEs